(untitled) - Cooper, Donald R. (New York, 2006)
There are several approaches to teaching marketing research. You could present the big picture and context first, and then break down the overall process into its parts. Or, you could start with techniques and build each into a phase of the overall process until at the end the overview is known. This book takes the approach that each student needs an overview first in order to appreciate the nuances and details of the specific techniques they will be asked to employ to develop high quality information. This belief led to the development of the text in four parts. The first part presents the overview, while parts 2, 3 and 4 provide the details on methodologies and techniques.
Keywords: Marketing research,Nghiên cứu tiếp thị